An investigation of risk management by the internal audit function: a case of city of Mutare’ - Matema, Luke (Midlands State University, 2017)
The research investigated risk management by the internal audit function-a case of Mutare City Council. A descriptive research was used while questionnaires and interviews research instruments were mainly used. The research has a sample size of twenty respondents. Graphs and tables were used for data presentation and the results were analyzed using measures of central tendency and hermeneutical analysis. The results show that the risk management policy does not exist at Mutare City Council. The staff that is responsible for the implementation of the risk management policy (directors, internal audit and finance) is not adequately trained for the implementation.A risk committee and a position of the chief risk officer do not exist at Mutare City Council. Based on findings, recommendations were made to the Mutare City Council. The recommendations include the creation of a risk committee and a position for the chief risk officer among others.